Model Manajemen Pendidikan Pesantren Berbasis Nilai untuk Pembentukan Kemandirian Santri - Nursaman (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study explores the implementation of pesantren-based management in shaping student autonomy at Pondok Pesantren Darul Ulum Karangpandan, Rejoso, Pasuruan. The research focuses on the role of kyai leadership, the structure of student self-reliance programs, and the internalization of pesantren values within the educational process. Employing a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that core pesantren values—such as sincerity, responsibility, and simplicity—serve as the foundation for managerial practices. The kyai plays a central role, functioning both as a spiritual leader and a policy director through a participatory leadership style. Programs including student cooperatives, entrepreneurship training, and daily task routines were shown to effectively foster both personal and social independence among students. The study affirms that value-oriented management rooted in pesantren culture offers a contextually grounded educational model that is both spiritually meaningful and practically effective. This model holds potential for replication in other pesantren with similar educational visions.